Pentingnya keterbukaan dan kejujuran dalam presentasi diri: Studi eksplorasi pengguna aplikasi Tinder - Bramanwidyantari, Maria; Helmi, Avin Fadilla (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2024)
Humans realize the importance of having a partner. However, the process in achieving this goal is challenging. Online dating became a medium to build romantic relationships that can be done easily through an application. The recognition process between users starts with liking each other's profiles which is assisted by an algorithmic system. So, it is important for users to present themselves properly on their profile. This study aims to see how the user's self-presentation is formed. Through a thematic analysis of the results of a questionnaire involving 383 Tinder online dating users, it was found that actual self-presentation is an important point for online dating users who emphasize aspects of honesty and openness. Differences in the motivation of online dating users do not lead to different self-presentation views between them. Moreover, the actual self in online dating profiles is displayed selectively taking into account the climate of informal interaction on Tinder.